A integração entre marketing e operações e o desempenho em inovação - Vicenzi, Jandir Balensiefer (2017)
The sustainability of a competitive position in the complex business-to-business market demands new ways to manage businesses, by integrating different functional competencies to reach a superior performance. In such a dynamic context, this dissertation aimed to investigate the impact of the integration between marketing and operations on innovation performance of the Brazilian flexible plastic packaging industry, contributing theoretically and empirically to organizational studies in the strategic marketing field. To reach the objective proposed, the methodological procedures were grounded on two steps, an exploratory qualitative approach and a descriptive quantitative one, through the construct presented by Song, Kawakami andStringfellow (2010), which had been previously applied with American and Japanese managers. The perceptions of commercial and marketing managers and production and operations managers, statistically analyzed through linear regression and correlation analysis, indicate that the integration between the functions has a positive and significant impact on product innovation performance, which converges with the perception of American and Japanese managers. The investigation of the functions’ integration level in each of the four steps of the new product development process indicated that information sharing between marketing and operations in the first step, “analysis of market opportunities”, and in the last step, “market launch of new products”, are the two steps in which the integration between the areas presents a positive and significant effect on the success of innovations. Marketing and operations were approached under a functional and non-departmental perspective, enabling the identification of historical conflicts between the areas, such as the structural separation of the activities and the focus on departmental goals, other than the company’s global objectives. The analysis also evidenced the lack of an effective and cooperative information sharing between the functions, a trend that is accentuated in more strategic stages of the new product development process. The different perceptions between marketing and commercial managers and production and operations managers was one of the main findings of this research, unveiling a vision antagonism between the areas regarding the impact of the fields integration on innovation success. The analysis indicated that marketing and commercial managers have a more short-term operational vision, focused on sales, evidencing the need for a strategic area responsible for disseminating a culture of market orientation between the functions aiming to reach superior long-term performance.